Teacher Understanding in Implementing Curriculum Change in Indonesia (International Journal of Scientific Research and Management (IJSRM), 2020)
Implementing a new curriculum really requires the creativity and independence of teachers. Especially in developing and implementing, it is not easy work to facilitate teachers when they not having strong understanding and the school does not facilitate this program. Some studies indicated that the initial implementation of curriculum changes was not effective. Teachers find that it difficult to implement changes in the form of teaching styles. The evidence from studies shows a lack of effort of teacher to implement change. There are various obstacles for teachers to implement curriculum changes. The obstacles indicate the form of weakness in terms of teacher skills and teacher knowledge. In curriculum change, weaknesses are found when the curriculum is prepared by other parties, or not by the teacher who guides the subject. The facts in the field show that not all teachers have the same understanding to compile a new curriculum. The ability of teachers is limited so that problems occur. Therefore, there is a need to pay attention on the understanding of teachers in implementing the curriculum change.